2018
DOI: 10.1037/xlm0000476
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements reveal persistent sensitivity to sound symbolism during word learning.

Abstract: Although the relationship between sound and meaning in language is assumed to be largely arbitrary, reliable correspondences between sound and meaning in natural language appear to facilitate word learning. Using a set of independently normed pseudoword and shape stimuli, we examined the real-time effects of sound-to-shape correspondences at initial presentation and throughout an extended learning process resulting in high accuracy. In addition to accuracy and response time (RT) measures, we monitored particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
(107 reference statements)
1
9
0
Order By: Relevance
“…Studies of sound-symbolic CCs also show that they are important for determining meaning across general categories. The findings from Gasser (2004) also indicate that the advantage of determining the specific meanings of words using sound symbolism is diminished as the vocabulary increases (although see Revill et al, 2018). Whether sound symbolism facilitates learning categories or specific word meanings in adults, the idea that sound symbolism can benefit adult learners has been recently validated with eye-tracking and other behavioral studies (Brand et al, 2018;Revill et al, 2018).…”
Section: Sound Symbolism In Language Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of sound-symbolic CCs also show that they are important for determining meaning across general categories. The findings from Gasser (2004) also indicate that the advantage of determining the specific meanings of words using sound symbolism is diminished as the vocabulary increases (although see Revill et al, 2018). Whether sound symbolism facilitates learning categories or specific word meanings in adults, the idea that sound symbolism can benefit adult learners has been recently validated with eye-tracking and other behavioral studies (Brand et al, 2018;Revill et al, 2018).…”
Section: Sound Symbolism In Language Acquisitionmentioning
confidence: 99%
“…For example, individuals exhibit sensitivity to sound-symbolic crossmodal associations as early as four months of age (Ozturk et al, 2013), and recent studies have suggested that sound symbolism is important for specific word-to-meaning associations in young children with limited vocabularies (Gasser, 2004;Tzeng, Nygaard, & Namy, 2017). In adults, sound symbolism may offer linguistic processing advantages for categorization and word learning, particularly for larger vocabularies (Brand et al, 2018;Gasser, 2004;Revill et al, 2018). Though most of the evidence supporting sound symbolism has consisted of behavioral studies, more recently neuroimaging studies have begun to reveal the neural correlates of this phenomenon (Revill et al, 2014;McCormick et al, 2018;Peiffer-Smadja & Cohen, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if a 2-year-old child encounters their very first tractor – say, a green John Deere working in a field – while hearing its name, the child from that point forward will recognize all variety of tractors as tractors – red Massey-Fergusons, antique tractors, ride-on mowers – but not backhoes or trucks. This phenomenon, known as the “shape bias” in the developmental literature is an example of “one-shot” learning that has been observed in children’s natural category learning and has been replicated and extensively studied in the laboratory (e.g., Rosch et al, 1976 ; Landau et al, 1988 ; Samuelson and Smith, 2005 ).…”
Section: What 2-year-olds Can Domentioning
confidence: 99%
“…Around 18 to 24 months (with the timing different for different children), the character and rate of learning changes. Around 2 years of age, object name learning becomes seemingly effortless as typically developing children need very little experience, often just a single experience with a named object, to generalize the name appropriately to new instances ( Landau et al, 1988 ; Smith, 2003 ). The shift from slow incremental learning to rapid nearly “one-shot” learning reflects changes in the internal machinery brought on by learning itself ( Smith et al, 2002 ).…”
Section: Self-generated Visual Experiencesmentioning
confidence: 99%